The theory-practice gap: epistemology, identity, and education. Issue 6 (5th August 2014) - Roth, Wolff-Michael; Mavin, Tim; Dekker, Sidney
Abstract : Purpose: – The purpose of this paper is to theorize the theory-practice gap and to provide examples of how it currently expresses itself and how it might be addressed to better integrate between the worlds of thought and praxis. Design/methodology/approach: – Two empirical examples exemplify how the theory-practice gap is an institutionally embodied social reality. Cultural-historical activity theory is described as a means for theorizing the inevitable gap. An example from the airline industry shows how the gap may be dealt with in, and integrated into, practice. Findings: – Cultural-historical activity theory suggests different forms of consciousness to exist in different activity systems because of the different object/motives in the world in which we think and the practical world in which we live. A brief case study of the efforts of one airline to integrate reflection on practice (i.e. theory) into their on-the-job training shows how the world in which pilots think about what they do is made part of the world in which pilots live. Practical implications: – First, in some cases, such as teacher education, institutional arrangements can be made to situate education/training in the workplace. Second, even in the training systems with high fidelity, high validity (transferability) cannot be guaranteed. Originality/value: – The approach proposed provides a theory not only for understanding the theory-practice gap but also the gap that exists even between very high-fidelity ("photo-realistic") training situations and the real-world praxis full of surprises.